A Brief History of Qinghaosu. Issue 12 (December 2015) - White, Nicholas J.; Hien, Tran T.; Nosten, François H.
Abstract : The 2015 Nobel Prize for Medicine or Physiology was awarded to William C. Campbell and Satoshi Ōmura for their discovery of avermectins, and to Tu You You for her contribution to the discovery of artemisinin. The discovery and development of qinghaosu (artemisinin) as an antimalarial drug is a remarkable and convoluted tale.